Peran Guru Dalam Mengelola Kelas di Lingkungan Sekolah Dasar Negeri Magersari 2 Kota Magelang - Putriani, Pingkan Dina (Prosiding University Research Colloquium, 2021)
This study aims to determine how the role of teachers in elementary schools. This research is a qualitative research The informant of this research is the fourth grade teacher of SDN Magersari 2 Data collection techniques are observation and interviews The result of the research is classroom management done by the teacher first arrange the students who are in the class, namely by making a class organizational structure, seating arrangements, decorations in the classroom, and cleanliness in the classroom. The teacher supervises the implementation the task of each student who is located in the class organization. After that proceed with the application of class management